Dynamics Matter: Recognition of Reward, Affiliative, and Dominance Smiles From Dynamic vs. Static Displays - Orlowska, Anna B.; Krumhuber, Eva G.; Rychlowska, Magdalena; Szarota, Piotr (Frontiers in Psychology, 2018)
Smiles are distinct and easily recognizable facial expressions, yet they markedly differ in their meanings. According to a recent theoretical account, smiles can be classified based on three fundamental social functions which they serve: expressing positive affect and rewarding self and others (reward smile), creating and maintaining social bonds (affiliative smile), and negotiating social status (dominance smiles) (Martin, Rychlowska, Wood, & Niedenthal, 2017; Niedenthal, Mermillod, Maringer, & Hess, 2010). While there is evidence for distinct morphological features of these smiles, their categorization only starts to be investigated in human faces. Moreover, the factors influencing this process – such as facial mimicry or display mode – remain yet unknown. In the present study, we examine the recognition of reward, affiliative, and dominance smiles in static and dynamic portrayals, and explore how interfering with facial mimicry affects such classification. Participants (N = 190) were presented with either static or dynamic displays of the three smile types, whilst their ability to mimic was free or restricted via a pen-in-mouth procedure. For each stimulus they rated the extent to which the expression represents a reward, an affiliative, or a dominance smile. Higher than chance accuracy rates revealed that participants were generally able to differentiate between the three smile types. In line with our predictions, recognition performance was lower in the static than dynamic condition, but this difference was only significant for affiliative smiles. No significant effects of facial muscle restriction were observed, suggesting that the ability to mimic might not be necessary for the distinction between the three functional smiles. Together, our findings support previous evidence on reward, affiliative, and dominance smiles by documenting their perceptual distinctiveness. They also replicate extant observations on the dynamic advantage in expression perception and suggest that this effect may be especially pronounced in the case of ambiguous facial expressions, such as affiliative smiles.